ELABORASI EKONOMI ISLAM DALAM KERANGKA FILSAFAT - Muhammad Satar; Amiruddin Kadir (JUPE : Jurnal Pendidikan Mandala, 2022)
Economics is known among the people for centuries. In Islam, economics was known intimately at the time of the Prophet Muhammad with the concept of trade that was present to suppress the economic development of the capitalism and socialism systems which became a problem in the welfare of society. The emergence of Islamic Economics in order to be able to solve economic problems that are rampantly controlled by the world with this system. So that the Islamic economic system is considered capable of providing a way out of the economic problems of the ummah and can provide welfare to the community. This paper aims to discuss more deeply about Islamic economics through a philosophical review and compare it with Western Economics. This study used the literature research method, how Islamic economics was formed with philosophical foundations starting from etymology, ontology and epistemology as well as the development and comparison of Islamic economic theory and other theories. This study reveals that the thing that distinguishes Islamic economics from other economics is the economic approach, both to fellow humans and to the creator (God), in contrast to other economic systems that prioritize profit or individual interests. Philosophy can be said to be in line with the Islamic economic system where in short philosophy has the meaning of love of wisdom which implies giving goodness to others.